Tinjauan Atas Penyusunan Anggaran Dan Pelaporan Realisasi Pada Perusahaan Umum Daerah Transportasi Pakuan Kota Bogor - Safitri, Hana Amelia; Pradipto, Didit; Efrianti, Desi (Program Vokasi dan LPPM IBI Kesatuan, 2024)
One of the supporters of the company in carrying out all its operational activities to the purpose and objectives of the firm is by the presence of a budget. Budgeting in the financing of a company is one of the important elements in the management of the company to maximum results. In addition to preparing a budget, the company also has an obligation to report on its implementation, so that the company can see the level of achievement of the company's targets. The purpose of this review is to know the preparation of the budget of the Municipal Transportation Company of Bogor and the reporting of the realisation of budget to the Municipal transportation company and to know how the treatment of the differences (variations) that occurred over the drafting of budget and reporting the realization in the Municipal Public Transportation Corporation of Bogore. Based on the results of the review it is known that the preparing of budget in the Regional Transportation Companies Bogor begins with the planning of budget until with the confirmation by the mayor and submission to the relevant ministries. Reporting of budget realisation to the Bogor Municipal Transportation District General Company is carried out every three months (3 months) or at the end of the period. Treatment of differences (variations) that occur over budget preparation and realization reporting, the company will make a change in the budget by making a Work Plan and Budget Changes (RKAP). Keywords: budgeting, realisation reporting